MAJOR TYPES, CHARACTERISTICS AND GEODYNAMIC MECHANISM OF UPPER PALEOZOIC COPPER DEPOSITS IN NORTHERN XINJIANG, NORTHWESTERN CHINA - Han C.; Xiao W.; Yan Z.; Mao Q.; Zhao G.; Mao J.; Li S. (My University, 2006)
Syn- and post-orogenic Cu mineralization in the northern Xinjiang Paleozoic accretionary and collisional orogenic belt in northwestern China is of great economic interest. About 40 Cu-bearing deposits have been discovered in the area, making it one of the most important metallogenic belts in China. According to their host rocks, these deposits can be classified into four principal types: (1) volcanic-hosted massive sulfide Cu-Pb-Zn deposits; (2) porphyry Cu-Mo-(Au) deposits; (3) magmatic Cu-Ni sulfide deposits; and (4) Cu-Mo-Au-Ag skarn deposits. Tectonically, the development of these Upper Paleozoic deposits was closely associated with subduction and collision of the ancient Asian Ocean between the Siberian Block and the Tarim Craton. An important metallogenic epoch involving formation of Cu-Pb-Zn-polymetallic deposits formed during southwestern rollback and associated slab-detachment during Devonian time (400-370 Ma). In southern Altay, southwestern-direct rollback and associated slab-detachment occurred during the Devonian (400-370 Ma), in response to later collision at the accreted continetal margin [Xiao, W.J., Windley, B.F., Badarch, G., Sun, S., Li, J.L., Qin, K.Z., Wang, Z.H., 2004. Palaeozoic accretionary and convergent tectonics of the southern Altaids: implications for the lateral growth of Central Asia. Journal of the Geological Society of London 161, 339-342], during which the Ashele Cu-Pb-Zn and Keketale Pb-Zn deposits formed. Subduction led to the accretion of the Junggar Ocean arc system in the Middle Devonian. In the Lower to Middle Carboniferous, north-dipping subduction beneath the Dananhu arc triggered the emplacement of granitic porphyries in the Tousuquan and Dananhu island arc belt in the east Tianshan, leading to the formation of the Tuwu and Yandong porphyry Cu-Mo-Au-Ag deposits. In the Upper Carboniferous to Lower Permian, large mafic-ultramafic complexes were emplaced during closure of the ancient Tianshan Ocean, resulting in the formation of several magmatic Cu-Ni sulfide deposits, including the Kalatongke Cu-Ni deposits in north Junggar and Cu-Ni sulfide deposits in the Huangshan-Jing'erquan area of east Tianshan Mountains. Also associated with this extensional event were emplacement of voluminous anatectic granitoids and eruption of volcanic rocks, which led to formation of skarn Cu-Mo (Suoerkuduk Cu-Mo deposit) and Cu-Ag deposits (Weiquan Cu-Ag deposit). The tectonic settings, geological features, and temporal and spatial distribution of these different types of Cu deposits reflect, to a great extent, the accretionary and collisional tectonics that occurred between the Siberian Block and Tarim Block. © 2005 Elsevier B.V. All rights reserved.
Keywords: CHINA; COPPER DEPOSITS; METALLOGENIC BELTS; TECTONIC SETTING; XINJIANG; Permian; Carboniferous; Devonian; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Devonian; Палеозой::Девонская